Mutational and non mutational adaptation of Salmonella enterica to the gall bladder - Urdaneta, Verónica (Sci Rep, 2019)
During systemic infection of susceptible hosts, Salmonella enterica colonizes the gall bladder, which contains lethal concentrations of bile salts. Recovery of Salmonella cells from the gall bladder of infected mice yields two types of isolates: (i) bile-resistant mutants; (ii) isolates that survive lethal selection without mutation. Bile-resistant mutants are recovered at frequencies high enough to suggest that increased mutation rates may occur in the gall bladder, thus providing a tentative example of stress-induced mutation in a natural environment. However, most bile-resistant mutants characterized in this study show defects in traits that are relevant for Salmonella colonization of the animal host. Mutation may thus permit short-term adaptation to the gall bladder at the expense of losing fitness for transmission to new hosts. In contrast, non mutational adaptation may have evolved as a fitness-preserving strategy. Failure of RpoS(−) mutants to colonize the gall bladder supports the involvement of the general stress response in non mutational adaptation.